The Influence of Infrastructure and Service Quality on Community Satisfaction at the Regional General Hospital Bumi Panua of Pohuwato Regency - Laksmin Kadir; Titin Dunggio; Syahrawanty Abbas (Journal of Economic, Business, and Administration (JEBA), 2021)
The influence of infrastructure and service quality on community satisfaction at the Regional General Hospital BumiPanua of Pohuwato Regency. This research aims to find out and analyze the influence of infrastructure and service quality on community satisfaction at BLUD of Regional General Hospital BumiPanua of Pohuwato Regency. This research uses a descriptive quantitative method. The sample in this research is the community and patients who have enjoyed services at BLUD of BumiPanua Hospital, Pohuwato Regency. Data analysis using multiple regression. The results of the research showed that the infrastructure has a positive and significant influence on community satisfaction. Service quality has a significant influence on community satisfaction. Infrastructure and service quality simultaneously have a positive and significant influence on community satisfaction.